N-(4-Chloro-3-nitrophenyl)maleamic acid - Sabine Foro; U. Chaithanya; B. Thimme Gowda (Acta Crystallographica Section E, 2012)
In the molecule of the title compound, C10H7ClN2O5, the acyclic C=C double bond is cis configured. The C=O and O—H bonds of the acid group are in a relatively rare anti position to each other, due to the donation of intramolecular hydrogen bond to the amide by the carboxyl group. The nitro group is significantly twisted [dihedral angle = 66.9 (3)°] out of the plane of the remaining atoms, which are almost coplanar (r.m.s. deviation for non-H atoms except the nitro group = 0.202 Å). In the crystal, N—H...O hydrogen bonds link the molecules into zigzag chains running along the b axis.